2016
DOI: 10.1155/2016/7570406
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy-Correlated Breast Imaging and Visual Grading Analysis Using Quantitative Transmission Ultrasound

Abstract: Objectives. This study presents correlations between cross-sectional anatomy of human female breasts and Quantitative Transmission (QT) Ultrasound, does discriminate classifier analysis to validate the speed of sound correlations, and does a visual grading analysis comparing QT Ultrasound with mammography. Materials and Methods. Human cadaver breasts were imaged using QT Ultrasound, sectioned, and photographed. Biopsies confirmed microanatomy and areas were correlated with QT Ultrasound images. Measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…We believe this is due to the ability of our algorithm to differentiate between glandular elements (speed values 1517-1567 m/s) from ductal tissue elements (speed values 1560 – 1612 m/s) as verified in [29] by histology. These TDLUs are ~1 – 4 mm in size.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…We believe this is due to the ability of our algorithm to differentiate between glandular elements (speed values 1517-1567 m/s) from ductal tissue elements (speed values 1560 – 1612 m/s) as verified in [29] by histology. These TDLUs are ~1 – 4 mm in size.…”
Section: Resultsmentioning
confidence: 75%
“…In other cases, we had observed that a low speed artifact of this type occurred internally as well, as shown in Figure 15. This anomalous speed value is substantially below even that of fat, and is problematic, since we have observed that solid lesions are characteristically higher speed (1570 m/s and higher) than fat, ductal, glandular tissue and complex or simple cysts[29]. Also, the attenuation in this 2D image was as high as 24 dB/cm/MHz.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations